Family Functioning in a Collectivist Culture of Malaysia: A Qualitative Study - Sumari, Melati; Khalid, Norfaezah Md; Ibrahim, Nor Hasniah; Ahmed Tharbe, Ida Hartina; Dini Farhana Baharudin (SAGE Publications Inc., 2024)
A family is a social unit in society. The societal culture where a family exists contributes to the functioning of the family. A review of the literature on family functioning indicates that most studies on family functioning were conducted by researchers in Western countries, particularly in the United States, and were conducted using a Western sample. In most studies, quantitative measurements were used to measure family functioning. No family measurement has been developed so far to measure family functioning in a collectivist culture such as that found in Malaysia. Therefore, we decided to use a qualitative approach in order to explore and understand family functioning in a collectivist society and focused on Malaysia as a case example. Focus group discussions were used to gather the data. Eleven family practitioners from different settings participated in a three-series discussion. Six themes emerged from the data analysis: (1) family role, (2) parenting styles, (3) family rule, (4) communication, (5) value orientation, and (6) cohesiveness. The method used yields rich data and highlights the importance of understanding an issue within its cultural context. The implication for family practitioners and future researchers is discussed. The Author(s) 2019.